2017
DOI: 10.1002/ldr.2784
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating Nitrogen Limitation in Mediterranean Maquis Vegetation Leads to Ecological Degradation

Abstract: Soils are being degraded at an alarming rate and thereby also crucial ecosystem goods and services. Nitrogen (N) enrichment is a major driver of this degradation. While the negative impacts of N enrichment on vegetation are well known globally, those on various ecological interactions, and on ecosystem functioning, remain largely unknown. Because Mediterranean ecosystems are N limited, they are good model systems for evaluating how N enrichment impacts not only vegetation but also ecological partnerships and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The values of V cmax and J max observed in our study are in agreement with previous studies reported for cork oak with contrasting water availabilities [36,37] or in studies with other Quercus or sclerophylls [26,38,39]. Similarly, the observed values of V cmax and J max for gum rockrose in our study were like those reported for gum rockrose during the summer in the only study that we are aware of [40], but also for other sclerophyllous shrubs [26,39,41].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The values of V cmax and J max observed in our study are in agreement with previous studies reported for cork oak with contrasting water availabilities [36,37] or in studies with other Quercus or sclerophylls [26,38,39]. Similarly, the observed values of V cmax and J max for gum rockrose in our study were like those reported for gum rockrose during the summer in the only study that we are aware of [40], but also for other sclerophyllous shrubs [26,39,41].…”
Section: Discussionsupporting
confidence: 92%
“…However, mesophyll conductance was also observed to decrease under drought conditions, potentially contributing to the reduction in apparent V cmax [4,26,37]. Despite cork oak showing high mesophyll conductance values (around 0.1 mol CO 2 m −2 s −1 ) compared to other evergreen oaks [26,37,53], the mesophyll conductance in gum rockrose [40] and other malacophylls is about double (> 0.2 mol CO 2 m −2 s −1 [26,37,41]. The contribution of mesophyll limitations for the whole non-stomatal limitations in each species remains to be clarified.…”
Section: Discussionmentioning
confidence: 97%
“…The low NUE may increase as the external concentrations of N, particularly nitrate, are reduced. Under natural Mediterranean conditions, a long-term N-manipulation study (since 2007) shows that N availability (and ammonium in particular) is a driving force for biodiversity changes above- [51,52] and belowground [53][54][55], suggesting that the biotic compartments (living plants, plant litter, soil biota) have a crucial role in preventing N losses [50]. Whether low NUE is actually a feature of plant species' response according to the availability of different N sources under natural environments [51,52] is still rather difficult to generalize, particularly for agro-ecosystems.…”
Section: Plant Nitrogen Use Efficiencymentioning
confidence: 99%
“…Thus, this paper presents a novel approach for using multivariate statistics of combined red, green and blue values to evaluate resistance to planthoppers. Previous studies have used similar methods for environmental assessments, such as evaluating phytotoxicity to grassland plants [64] or the impact of nitrogen enrichment on Mediterranean maquis vegetation [65].…”
Section: Plos Onementioning
confidence: 99%